Comparison between human olfactory sensitivity in the fasted and fed states: A systematic review and meta-analysis. (1st February 2023) - Nie, Haoyu; Zhao, Rong; Ai, Yun; Yang, Yingkai; Cao, Bing; Han, Pengfei
Abstract: Introduction: Olfaction is tightly regulated by internal status such as hunger level. The influence of fasted and fed states on olfactory sensitivity in humans has reached mixed results. This study aims to systematically review, integrate and meta-analyze evidence of the impact of fasting on olfactory sensitivity in humans and to explore the impact of potential moderators. Method: Electronic databases (PubMed, PsycINFO, Web of Science, COCHRANE and Ovid) were searched for studies with human participants investigating the effect of fasting on olfactory sensitivity. Studies were included in the review if they measured odor threshold both at fasted and sated status. The data extraction was determined based on the change in odor threshold from the fasted state to the fed state. Meta-analysis was conducted using a random-effect model to estimate the standardized mean difference transformed olfactory sensitivity change between fasted and fed states with 95% confidence interval (CI). Results: Thirteen studies (12 articles) were included in the meta-analysis with a total of 550 participants. Olfactory sensitivity was higher in the fasted state compared to the fed state (SMD = −0.251, 95% CI = −0.426, −0.075, Z = −2.804, p = 0.005). Separated analyses for food and non-food odors revealed a significant elevated sensitivity to non-food odors during the fasted state compared to the fed state. The meta-regression analysis revealed that fasting time positively moderate the increased olfactory sensitivity from the fasted to fed states (β = −0.013, 95% CI = −0.023, −0.002, p = 0.016). Conclusion: Fasting improves human olfactory sensitivity to non-food odors, and this effect increases with longer fasting time. Future research design on olfactory sensitivity should take both the fasted state and fasting period of the participants into consideration.